The biomimetic potential of novel adaptations in subterranean animals - Hesselberg, Thomas (Frontiers in Ecology and Evolution, 2023)
Subterranean habitats can be considered harsh conditions with lack of light, low nutrients levels and constant high humidity. To thrive under such conditions, cave-adapted species have evolved a range of novel morphological, physiological and behavioural adaptations. These adaptations might have significant biomimetic potential. Biomimetics or biologically inspired design is a relatively new interdisciplinary field that aims to harness the processes and mechanisms in nature that have been optimised over millions of years' evolution to improve our own technology. There are two main approaches to biologically inspired design-the problem-driven approach starting with an engineering problem and searching through biological equivalents and the solution-driven approach, which starts with a biological example or solution followed by the identification of a suitable engineering application. While the former approach is the most popular and is favoured by engineers, the latter remains the most successful and is typically driven by fundamental biological research. However, few biomimetic solutions or concepts have so far been described from subterranean habitats despite the rich potential. In this review paper, I first outline the theory behind biologically inspired design before I review the few biomimetic related studies of cave adapted organisms mainly based on the exceptional lateral line systems in blind cave fish. However, the main body of the review focuses on identifying and discussing subterranean adaptations with a particular strong potential including biomimetics sensors, adhesion in high humidity and wet conditions and biomaterials.